Financial crisis: Deposit insurance and related financial safety net aspects - Schich, Sebastian (OECD Publishing, 2009)
Government provision of a financial safety net for banks and other financialinstitutions has been a key element of the policy response to the current financialcrisis. In the process, the design of many safety net elements, such as depositinsurance, has been redrawn in many jurisdictions. In particular, governmentsextended existing guarantees and introduced new ones. While these measures didnot address the root causes of the lack of confidence, they were neverthelesshelpful in avoiding a further accelerated loss of confidence, thus buying valuabletime